A rare case of Spigelian Hernia, Diagnosis and Treatment - Wafa Hassan; Waqas Ahmed; Saeed Ahmed Khan Nurejo (ziauddin University, 2024)
Abstract: As it stands, Spigelian hernias are rare and generally overlooked or misdiagnosed. We report a case in which a Spigelian hernia presented to us as a painless abdominal swelling in a 39 year old obese female with no known co-morbids The hernia appeared as swelling in the right lower quadrant, which was non tender at the time of admission and showed no signs of strangulation. Diagnosis of the hernia was made on CT-scan and an open technique was adapted to repair it. The post op period was insignificant in the patient. Key Words: Spiglelian Hernia, Hernia, Spigelian Fascia Defect.